Do responsible real estate companies outperform their peers? - Cajias, Marcelo; Fuerst, Franz; McAllister, Patrick; Nanda, Anupam (International Journal of Strategic Property Management, 2014)
This paper investigates the relationship between corporate social and environmental performance and financial performance for a sample of publicly traded US real estate companies. Using the MSCI ESG (formerly KLD) database on seven Environmental, Social & Governance dimensions in the 2003–2010 period, and weighting the dimensions according to prominence in the real estate sector, we model Tobin’s Q and annual total return in a panel data framework. The results indicate a positive relationship between ESG rating and Tobin’s Q but this effect is driven by ESG concerns rather than strengths. Consistently across all model specifications, overall ESG ratings are associated with lower returns. Negative scores appear to result in higher returns, at least in the short run, but positive scores have no significant impact on returns. First Publish Online: 21 Mar 2014